2018
DOI: 10.1136/jech-2018-210487
|View full text |Cite
|
Sign up to set email alerts
|

A decade lost: does educational success mitigate the increased risks of premature death among children with experience of out-of-home care?

Abstract: BackgroundPast research has consistently identified children with out-of-home care (OHC) experience as a high-risk group for premature mortality. While many have argued that educational success is a key factor in reducing these individuals’ excessive death risks, empirical evidence has hitherto been limited. The aim of the current study was therefore to examine the potentially mitigating role of educational success in the association between OHC experience and premature mortality.MethodsDrawing on a Stockholm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…For example, an earlier study based on the SBC Multigen found that above-average school performance counteracted the increased risks for premature mortality among individuals with childhood experiences of out-of-home care. 24 Another study, drawing on information from the Northern Swedish cohort, found that adversity during adolescence was less strongly associated with having poorer self-rated health in midlife among individuals who had an advantaged situation with regard to school, peers or spare time. 25…”
Section: Discussionmentioning
confidence: 99%
“…For example, an earlier study based on the SBC Multigen found that above-average school performance counteracted the increased risks for premature mortality among individuals with childhood experiences of out-of-home care. 24 Another study, drawing on information from the Northern Swedish cohort, found that adversity during adolescence was less strongly associated with having poorer self-rated health in midlife among individuals who had an advantaged situation with regard to school, peers or spare time. 25…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should aim at explaining the remaining part of the association by considering other indicators of disadvantage, measured from adolescence and onwards, such as behavioural problems, poor housing, somatic ill-health, low general well-being, early childbearing and family disruption, and poor educational attainment. In particular, past research has identified educational failure as a fundamental explanation for the adverse long-term outcomes of child welfare clients [9, 2123].…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the context of the current study, a core aim of OHC placement is also to provide the child with better opportunities for development [2]. Yet, prior research has consistently identified children with experience of OHC as a high-risk group for premature mortality [39], the perhaps most readable indicator of health inequality.…”
Section: Introductionmentioning
confidence: 99%
“…In a Danish study, the mortality risk was approximately three times higher in the OHC population compared to peers in the majority population at the age of 27, with adjustment for parental background factors including psychiatric disorders, substance misuse, educational attainment, and unemployment (Nygaard Christoffersen 1999). Almquist et al (2018) found that the OHC population lost almost a decade in life expectancy between the ages of 20 and 56 in comparison to peers in the majority population without OHC experience, and that school failure was strongly associated with the excess mortality. Evidence suggests that the risk factors for school failure and excess mortality are similar and intertwined with, for instance, behavioural disorders, substance misuse, and mental health problems including suicidal behaviour (Manninen et al 2015;Nygaard Christoffersen 1999;Hjern, Vinnerljung, and Lindblad 2004;Kalland et al 2001;Berlin, Vinnerljung, and Hjern 2011).…”
Section: Previous Research On Predictors Of Mortality In the Ohc Popumentioning
confidence: 99%